Penerapan Personal Branding “Venny Eriska” Sebagai Lifestyle Influencer dan Blogger Medan di Media Sosial Instagram - Utami, Anggun (KESKAP: Jurnal Kesejahteraan Sosial, Komunikasi dan Administrasi Publik, 2024)
Current developments in information technology, especially in social media. Paying attention to and building a good personal brand in this technological era is very important, considering the increasingly complex nature of competition. One way to show brand identity is through personal branding, which is a process for someone to manage and control other people's perceptions of the individual brand they are building. This research aims to find out how the personal branding "Venny Eriska" is implemented as a Medan lifestyle influencer and blogger on instagram social media. The research method used in this research is a qualitative method where the data results are not obtained through statistical procedures or in other forms of calculations which leads to non-mathematical data analysis. Data collection techniques are carried out using observation, interviews, and documentation. The stages of data analysis techniques in this research are data reduction, data presentation, and conclusion drawing. The results of the research conducted by the author in this study refer to the six keys to success namely, distinctiveness, relevance, consistency, competency/ ability, style, and meaning renewal standards.